Perspectives in increasing attractiveness of Bukhara destination by establishing the Bukhara Bureau of Convention and Exhibition (BBCE). - Kuvandikov Aziz Ravshanovich (Peerian Journals Publishing, 2024)
One of the major reason is that at the beginning of the XXI century tourism started prospering sharply in uzbekistan and especially new era of developing tourism industry began in 2017.The second President of Uzbekistan Mirziyoyev Sh.M declared –tourism as main engine of economy in Modern Uzbekistan and by this aim there were signed the following documents; 1) decree of the President of the Republic of Uzbekistan, referring to 05.01.2019 year № DP-5611 on additional measures for the accelerated development of tourism in the Republic of Uzbekistan, Presidential Decree of the Republic of Uzbekistan of april 6, 2021 №-6199 “About measures for further enhancement of system of public administration in spheres of tourism, sport and cultural heritage”of the President of Uzbekistan, PD-135 signed on 26.04.2023” About additional measures to accelerate the development of the tourist potential of the republic, as well as further increase in the number of local and foreign tourists in the republic of Uzbekistan “ and the latest one was signed on July 27, 2023 No. PP-238 “About measures for further acceleration of reforms and the effective organization of system of public administration in the sphere of tourism in the territory of Uzbekistan”.
Keywords: Bukhara city on Silk Road; Uzbekistan Chamber of commerce and industry; Development Strategy of New Uzbekistan